Kaviar-Sensorik - Lehmann, Ines (2009)
For determining the quality of caviar the use of human senses is the best choice. In the literature only a couple of attributes for description of caviar were found. In this work we have built a comprehensive profile of attributes in German for the description and the evaluation of the quality of caviar. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung - Information Fishery research in 2010. Max Rubner-Institut (MRI), Institut für Sicherheit und Qualität bei Milch und Fisch